Правове виховання – важлива частина соціалізації особи - Жаровська, І.; Zharovska, I. (Східноєвропейський національний університет імені Лесі Українки, 2017)
В статті розглядаються аспекти взаємодії таких юридичних явищ як правове виховання і правова соціалізація. Доведено, що найважливішою загальною ціллю правового виховання є правова соціалізація особи. Визначено, що правове виховання здійснюється шляхом цілеспрямованої правової пропаганди, освіти і навчання, самоосвіти. The article highlights the aspects of the interaction of such legal phenomena as legal education and legal socialization. It is proved that the most important and universal goal of legal education is the legal socialization of a person. The author argues that to enhance the efficiency of legal socialization, legal activity and legal culture of society members it is necessary to intensify purposeful, planned, targeted activities on the part of the state and its authorized bodies. Legal socialization is not only the formation of the skills of social behavior, relevant to the legal norms of the society, but also the «subjectivization» of such norms, the emergence of the internal motivation, which encourages every person to observe them. Legal education is ideologically-biased, since it imposes certain legal regulations on people's activity, consciousness and is aimed at forming a legal culture of every person. Legal socialization contributes to the appropriate level of legal activity. The above mentioned arguments give grounds to draw the conclusion that legal education shapes an «active2 legal personality with a solid legal and political position, forming internal belief that law is an ethic and moral social category. It is determined that legal education is realized through purposeful legal propaganda, education and training, and involves self-education.
Legal Education as an Important Integral Part of a Person’s Socialization
Keywords: правове виховання; правова соціалізація; правова пропаганда; правова освіта; правове навчання; legal education; legal socialization; legal propaganda; legal education; legal training